Republic of Senegal : Safety Net Assessment - World Bank (Washington, DC, 2014)
In 2010, the World Bank initiated a technical assistance program in social protection with the Government of Senegal, with a focus on safety nets. The World Bank and the government identified a number of technical notes and training sessions tailored to the immediate needs of the government. This Senegal safety net assessment integrates and summarizes the content of these technical notes. Poverty is a serious concern in the country, with the economy displaying significant vulnerabilities. While the government has been quick to respond to past crises, some of the measures taken by the government have had certain drawbacks. Also, factors such as poorly targeted support and rising prices have detracted from the efforts taken by the government. A well designed and implemented national safety net system is thus of utmost importance. This document examines the various factors involved in the creation and implementation of a well-designed safety net system for Senegal.